Anti acne-causing bacteria and phytochemical studies of jambu batu (Psidium guajava Linn.) leaf - Md Padzil, Khairul Naim (2020)
Acne vulgaris is a noticeable skin disorder in human that can be found on the face, on either back or on chest. Four main factors causing acne are bacteria, excess oil production, hair follicles clogged by oil and dead skin cells, and excess activity of a type of androgen hormone. The medicines to treat acne vulgaris mostly focused on its efficacy of antibacterial and antioxidant activities. Recently, there is increasing interest to use natural product from plant extracts to inhibit the growth of acne-causing bacteria. The aims of this study were to determine the antibacterial activity of Psidium guajava Linn. extracts and fractions against three major acne-causing bacteria, namely Staphylococcus aureus KCCM12255, Staphylococcus epidermidis KCCM40003 and Propionibacterium acnes KCTC3314, to determine the antioxidant of P. guajava Linn. of the extracts and its fractions and to identify the potential anti-acne metabolites in P. guajava Linn. The antibacterial activities were determined using standard methods of Clinical and Laboratory Standard Institute (CLSI), in term of disc diffusion assay, minimal inhibitory concentrations (MICs), minimum bactericidal concentrations (MBCs) and time kill assay. Total phenolic content (TPC) and antioxidant activity of P. guajava Linn. were determined using Folin-Ciocalteau assay and 2,2-diphenyl-1-picrylhydryzyl (DPPH) assay, respectively. The active compounds anti-acne in fractions were identified by using Gas Chromatography-Mass Spectrometry (GS-MS), Liquid Chromatography-Mass Spectrometry (LS-MS) and Proton Nuclear Magnetic Resonance (1H NMR). The leaves of P. guajava Linn. was extracted into crude extract using four different solvents, namely methanol, ethanol, hexane and water. Moreover, methanolic extract was fractionated using four different solvents: hexane, chloroform, ethyl acetate and aqueous methanol. The results showed that disc diffusion assay of crude extracts and fractions showed that the range of inhibition zone were 8.50 ± 0.17 to 12.50 ± 0.41 mm and 8.45 ± 0.15 to 12.65 ± 1.55 mm, respectively. The P. guajava Linn. leaves extracts and its fractions have been able to inhibit the bacterial growth at MICs ranged from 0.31 ± 0.00 to 2.08 ± 0.59 mg/mL and 0.21 ± 0.07 to 4.17 ± 1.18 mg/mL, respectively. The extracts or fractions have been able to kill the bacteria with MBCs at values ranged from 0.63 ± 0.00 to 4.17 ± 1.18 mg/mL and 0.63 ± 0.00 to 4.17 ± 1.18 mg/mL, respectively. Time-kill curve analysis showed that bactericidal endpoint of all tested bacteria can be killed completely with ranged concentration of 4× MIC (0.21 mg/ml – 4.16 mg/ml) for four hours. Total phenolic content of the extracts ranged from 441.18 ± 18.21 to 147.1 ± 4.27 mg of GAE/g of dried weight material. The DPPH assay showed IC50 of the extracts at the range from 124.66 to 217.87 μg/mL. The ten volatile compounds were found, as determined using GC-MS, are E-caryophyllene, β-selinene, α-selinene, α-humulene, globulol, aromadendrene, p-cymene, pyrogallol, 2,4-bis(tert-butyl)-phenol and oleic acid. Moreover, LC-MS has identified fifteen non-volatile compounds, namely α-linolenic acid, stearic acid, betulinic acid, ursolic acid, lupeol, myricetin, epicathecin, quercetin, syringic acid, 4-coumaric acid, luteolin, maslinic acid, asiatic acid, γ-tocopherol and caryophyllene oxide. An active metabolite has been identified based on the 1H NMR, which is quercetin. In conclusion, P. guajava Linn. extracts and its compounds showed a promising potential of antibacterial activity against the acne-causing bacteria and antioxidant activity, thus it might be developed as natural anti-acne agents.